Evaluating the Effect of (W) Angle and ANB Angle in the Assessment of Anterioposterior Jaw Relationship and their correlation to gonial angle - Zaid Burhan Al-Dewachi (University of Mosul, College of Dentistry, 2018)
Aims: to evaluate the accuracy of W angle, ANB angle and gonial angle in assessing anterio-posterior jaw dysplasia and the correlation between them in class I , II, III patients. Materials and Methods: one hundred twenty patients (18-30) years of male and female from the center of Mosul City that met the criteria of the sample with class I, II, and III, the sample was divided into 3 groups The: 40% was male (48 cases) and 60 % was female (72 cases). Three groups 40 cases were distributed for each one of class I, II, III. Cephalometric analysis and measurement of angles were done .Results: the mean value of gonial angle for class I was 126.24±0.77° , class II cases was 123.42±0.86° and the class III cases was 127.53±0.98°;the mean value of W angle for class I was 53.953±0.309° , for class II was 48.78±1.29° and for class III was 60.96±3.00; 3; the mean value of ANB angle for class I was 2.71±0.155° , class II was 5.82±0.431°and for the class III was -3.182±0.241.The comparison between all variables in all classes showed highly significant differences at p